Specific domains of early parenting, their heritability and differential association with adolescent behavioural and emotional disorders and academic achievement. - Culpin, Iryna; Bornstein, Marc H.; Putnick, Diane L.; Sallis, Hannah; Lee, Ruby; Cordero, Miguel; Rajyaguru, Priya; Kordas, Katarzyna; Cadman, Tim; Pearson, Rebecca M. (European Child & Adolescent Psychiatry, 2020)
Variations in parenting across large populations have rarely been described. It also remains unclear which specific domains of parenting are important for which specific offspring developmental outcomes. This study describes different domains of early parenting behaviours and their genetic heritability, then determines the extent to which specific domains of parenting are associated with later offspring outcomes. Parenting behaviours (birth to 3 years) were extracted from self-reported questionnaires administered to 12,358 mothers from the UK-based birth cohort study, the Avon Longitudinal Study of Parents and Children and modelled as a latent factor using Confirmatory Factor Analysis. Genetic heritability and correlations between parenting factors were estimated using genome-wide complex trait analysis. Three parenting factors were derived: parental enjoyment, conflictual relationships and stimulation; all showed low genetic heritability. There was no evidence of association between parental enjoyment and offspring behavioural disorders and depressed mood. Stimulation was associated with better English grades (standardised β = 0.195, p < 0.001) and enjoyment was negatively associated with English grades (β = − 0.244, p = < 0.001). Conflictual relationships were associated with higher risk of offspring behavioural disorders (β = 0.228, p = 0.010) and depressed mood (β = 0.077, p = 0.005). Higher enjoyment reduced the association between conflict and behavioural problems (interaction term β = 0.113, p < 0.001). We found evidence for predictive specificity of early parenting domains for offspring outcomes in adolescence. Early stimulation, unlike enjoyment, promoted later educational achievement. Conflictual relationships were associated with greater risk of behavioural problems, buffered by increased enjoyment. These findings hold implications for parenting interventions, guiding their focus according to the specificity of parenting domains and their long-term outcomes in children.